A Web‐based Decision Support System for Managing Panicle Caterpillars in Sorghum. Issue 1 (1st September 2014) - Backoulou, G. F.; Elliott, N. C.; Royer, T. A.; McCornack, B. P.; Giles, K. L.; Pendleton, B. B.; Brewer, M. J.
Abstract : Panicle caterpillars are economically important pests of sorghum throughout the Great Plains of the United States. Sorghum producers, crop consultants, and extension professionals desire to manage panicle caterpillars to minimize economic loss. To manage panicle caterpillars in this manner, sorghum fields must be sampled to facilitate optimal control decisions for this pest complex. The decision support system (DSS) described here contains a simple expert system to calculate the economic threshold for panicle caterpillars in any sorghum field. This article reports the development of the DSS, which is based on a knowledge representation model that is easy to use and requires no specialized training. Our web‐based DSS application is accessible through most web browsers on personal computers having access to the Internet.